Thiol groups of soybean callus succinyl CoA synthetase - De Xifra, E.A.W. (1974)
1. 1. The reaction between 5,5′-dithio-bis-(2-nitrobenzoic acid) (DTNB) and the SH groups of soybean callus succinyl-CoA synthetase has been investigated. At pH 8-6 and 25° C, four SH groups are titrable with DTNB in the native enzyme. No additional thiol groups have been revealed after unfolding of the protein with 8 M urea. 2. 2. The loss of enzymatic activity paralleled the decrease in the number of free SH groups. As with p-mercuribenzoate and other mercurials, reaction with DTNB also resulted in dissociation of the enzyme into subunits. © 1974.